Immunophenotypic investigation of infant acute lymphoblastic leukemia - A. M. Popov; G. A. Tsaur; T. Yu. Verzhbitskaya; O. V. Streneva; E. V. Shorikov; L. I. Saveliev; L. G. Fechina (Онкогематология)
Aim of the study – immunophenotype description of infant acute lymphoblastic leukemia (ALL). 64 patients (29 boys and 35 girls) with acute leukemia (AL) aged from 0 to 11 months were included in the current study. ALL was found less frequently in infants than in older children (67.19 % and 87.69 %, respectively). BI-ALL was the most common immunological ALL type (60.46 %) in infant ALL, while BII-ALL was notably less frequent compared with other age groups (30.23 %). Significant immunophenotypic differences were observed in patients with and without MLL gene rearrangements. Number of cases in those tumor cells expressed CD10, CD20, CD45, CD133, CD15, NG2 varied between MLL-positive and MLL-negative groups. CD10- and CD20-negativity, high CD45, CD15, CD65 and NG2 expression were immunophenotypic signatures of MLL-rearranged infant ALL, although NG2 had the highest diagnostic efficacy. High CD34 and CD65 expression was frequently associated with presence of MLL-AF4 fusion gene. Thus infants’ B-cell precursor ALL immunophenotype differs significantly due to the presence of MLL gene rearrangements. Diagnostic immunophenotyping of infants’ ALL allows predicting presence of MLL rearrangements and NG2 is the most applicable single marker.